New species of Burmeistera (Campanulaceae: Lobelioideae) from Ecuador - Vallejo, Andrea F.; Pérez, Álvaro J.; Cevallos, Daniela; Muchhala, Nathan (Phytotaxa, 2018)
Two new species of Burmeistera endemic to Ecuador are described and their relationship with other species are discussed. Burmeistera pterifolia has an extremely narrow distribution on the northwestern foothills of the Andes in the Pichincha province, and it is easily differentiated from its congeners by its pinnatilobate leaf margin and large calyx lobes. The second species, Burmeistera draconis, is recorded from the Zamora Chinchipe province. It is distinctive in possessing an irregularly bidentate leaf margin and cylindrical inflated fruits with short calyx lobes.